Analysis Bibliometrics Application of Technology Acceptance Model in Islamic Fintech - Pulungan, Ismail; Ritonga, Juliani; Binti Abu Hasan, Nurul Widad (Journal of Islamic Financial Technology, 2024)
ABSTRACT          The rapid advancement of technology has led to the emergence of Islamic fintech as an innovation in digital financial services with the potential to enhance financial inclusion. However, public understanding of its use remains limited, resulting in cases of misuse and losses for users and companies alike. This study aims to analyze the factors influencing the acceptance of Islamic fintech using bibliometric methods. Employing a qualitative descriptive approach, data was collected through the Publish or Perish software and analyzed using VOSviewer to map the development of research on the Technology Acceptance Model (TAM) in Islamic fintech. The findings reveal significant growth in Islamic fintech journal publications in 2020, with "fintech" being the most frequently used keyword. Furthermore, the author analysis identifies Rabbani as the primary contributor. Research on the application of TAM in Islamic fintech remains scarce, but this model has proven effective in predicting technology acceptance. By understanding the factors influencing technology acceptance, companies can develop better strategies to expand their user base and enhance consumer trust in their services. Keywords: TAM, Islamic Fintech, Bibliometric, VOSviewer